2020 ASHRAE handbook : heating, ventilating, and air-conditioning systems and equipment (ASHRAE, 2020)
The 2020 ASHRAE Handbook--HVAC Systems and Equipment discusses various systems and the equipment (components or assemblies) that comprise them, and describes features and differences. This information helps system designers and operators in selecting and using equipment. Major sections discuss air-conditioning and heating systems; equipment and components for air handling, heating, cooling, and general application; packaged, unitary, and split-system equipment; and general systems.
Keywords: Heating -- Handbooks, manuals, etc.; Heating -- Equipment and supplies -- Handbooks, manuals, etc.; Ventilation -- Handbooks, manuals, etc.; Ventilation -- Equipment and supplies -- Handbooks, manuals, etc.; Air conditioning -- Handbooks, manuals, etc.; Air conditioning -- Equipment and supplies -- Handbooks, manuals, etc.; elektronické knihy; electronic books